Cover Feature: 3D‐Printed Structured Reactor with Integrated Single‐Atom Catalyst Film for Hydrogenation (ChemCatChem 14/2022). Issue 14 (30th June 2022) - Vilé, Gianvito; Ng, Derrick; Xie, Zongli; Martinez‐Botella, Ivan; Tsanaktsidis, John; Hornung, Christian H.
Abstract : The Cover Feature artistically shows the immobilization of a thin single‐atom catalyst film on 3D‐printed metal structures. As discussed in their Research Article, G. Vilé and co‐workers first prepared a powdered copper single‐atom catalyst. Then, they used 3D printing with an electron beam melting method to create a static mixer reactor coated with the single‐atom catalyst film. The resulting catalytic reactor was used for continuous hydrogenations, with stable performance for several hours on stream. Industrially, structured catalytic reactors have several advantages compared with traditional packed‐bed reactors, including low catalyst inventory, low pressure drop, and efficient mass/heat transfer. Thus, this work may have implications for the large‐scale utilization of these catalytic materials. The authors thank Carmelo (Il Merlo) Garofalo for the illustration.More information can be found in the Research Article by G. Vilé and co‐workers .